(untitled) - Paskusz, Gerhard F. (Englewood Cliffs, N.J., 1963)
1. Elementary concepts, 2. Analogies, 3. Circuit equations and properties of solutions, 4. Laplace transform solutions,...
Keywords: Electric circuits,Mạch điện